Harmonic Patterns in Forex Trading - Nemček, Sebastian; Žilák, Pavel; Fičura, Milan; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2013)
This diploma thesis is committed to examination of validity of Harmonic Patterns in Forex trading. Scott Carney described existing and introduced new Harmonic Patterns in 1999 in his book Harmonic Trader. These patterns use the Fibonacci principle to analyze price action and to provide both bullish and bearish trading signals. The goal of this thesis is to find out whether harmonic trading strategy on selected pairs is profitable in FX market, which patterns are the most profitable and what is the success rate for the signals they provide.
Vedoucí práce: Pavel Žilák
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: finance [obor dipl. práce]; diplomové práce; master's theses